2013
DOI: 10.1016/j.pec.2013.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Physician communication styles in initial consultations for hematological cancer

Abstract: Objective To characterize practices in subspecialist physicians’ communication styles, and their potential effects on shared decision-making, in second-opinion consultations. Methods Theme-oriented discourse analysis of 20 second-opinion consultations with subspecialist hematologist-oncologists. Results Physicians frequently “broadcasted” information about the disease, treatment options, relevant research, and prognostic information in extended, often-uninterrupted monologues. Their communicative styles ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 19 publications
1
38
0
Order By: Relevance
“…Physicians are known to be among the most important sources for cancer patients, providing them with medical and emotional support (Chhabra et al 2013). Nevertheless, relatively few studies have examined the correlations between communication styles and health outcomes among oncology patients (Ong et al 1998); literature review indicates even fewer focusing on older patients.…”
Section: Goals Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Physicians are known to be among the most important sources for cancer patients, providing them with medical and emotional support (Chhabra et al 2013). Nevertheless, relatively few studies have examined the correlations between communication styles and health outcomes among oncology patients (Ong et al 1998); literature review indicates even fewer focusing on older patients.…”
Section: Goals Of the Studymentioning
confidence: 99%
“…type of communication (Chhabra et al 2013). Previous studies identified two major communication styles: a task-focused communication style and a relationshipbuilding-focused communication style.…”
mentioning
confidence: 99%
“…The expressed need to learn how to tailor and structure information-giving aligns with the finding that, in a hematology setting, physicians tend to use lengthy monologues of standardized information, insufficiently tailored to patient needs, hoping to convey as much relevant information as possible in a restricted time [ 43 ]. Participants in our study seem to be conscious that this may lead to information overload, which in turn increases patients’ anxiety and hampers patients’ understanding and recall of information.…”
Section: Discussionmentioning
confidence: 99%
“…However communication skills are reported to remain a challenge for haematologists (Alexander et al , ; Chhabra et al , ). Research has shown a tendency to ‘broadcast’ using monologues, particularly during bad news delivery in haematological cancer consultations (Chhabra et al , ). Whilst Alexander et al () described a tendency to neglect the patient's role in decision making and information preferences, there is also evidence that haematologists do not feel confident with their level of training in communication skills, with many reporting low levels of satisfaction with the degree of training they receive or the methods used before qualification (Kersun et al , ; File et al , ).…”
Section: Art Versus Sciencementioning
confidence: 99%